Pengembangan Sistem Informasi Penetapan Angka Kredit Guru (Studi Kasus: Dinas Pendidikan Kota Malang) - Dimas Bhayu Primarizki; Herman Tolle; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on Permen PAN-RB No.16 Tahun 2009, teacher promotion systems are calculated using credit grades, which are calculated according to the workload and activities of the teacher in the assessment period. In each period the number of submissions can reach hundreds. Every single data must go through the process of checking the completeness and validity of files, as well as the recapitulation manually. This conditions are felt to be very inefficient and waste a lot of time. Therefore an information system is needed to deal with the problem. The process of checking and recapitulation can be facilitated by using the Sistem Informasi Penetapan Angka Kredit Guru that is built using the waterfall method and implemented on the website platform. Furthermore, testing is carried out using validation testing, compatibility testing, and usability testing. The results of validation testing that have been done show that the system can work properly according to its functionality. As for the results of compatibility testing, the system can run well on several different browser versions. Then from the results of usability testing, shows that the system gets B grades which means it can be easily used by the user.